Effects of empagliflozin on conventional and exploratory acute and chronic kidney outcomes: an individual participant-level meta-analysis - Herrington, William G.; Che, Zhaojing J; Sardell, Rebecca; Roddick, Alistair J; Judge, Parminder K; Wanner, Christoph; Hauske, Sibylle J.; Anker, Stefan; Butler, Javed; Filippatos, Gerasimos; Packer, Milton; Zannad, Faiez; et al. (The lancet. Diabetes & Endocrinology, 2025)
Background - Uncertainty remains about effects of sodium-glucose co-transporter-2 (SGLT2) inhibition on kidney outcomes in individuals with slowly progressive chronic kidney disease (eg, low albuminuria) and those at risk of large acute estimated glomerular filtration rate (eGFR) dips on initiation of such treatment. We aimed to explore the effects of empagliflozin on a range of kidney outcomes in these population subtypes. - Methods - In this meta-analysis, we used individual-level data from 23 340 participants in four large placebo-controlled trials (EMPA-REG OUTCOME, EMPEROR-Reduced, EMPEROR-Preserved, and EMPA-KIDNEY) to assess the effects of empagliflozin on conventional and exploratory acute and chronic kidney outcomes. We then assessed whether effects varied by predicted size of the acute eGFR dip on treatment initiation or among other key population subtypes using tests for heterogeneity and trend. The individual-level data were requested from Boehringer Ingelheim (Ingelheim, Germany). - Findings - Compared with placebo, allocation to empagliflozin reduced the risk of a marker of acute kidney injury (a ≥50% increase in serum creatinine in consecutive follow-up samples) by 20% (hazard ratio 0·80 [95% CI 0·72-0·88]; 1573 outcomes), acute kidney injury adverse events by 27% (0·73 [0·63-0·85]; 694 outcomes), a categorical chronic kidney disease progression outcome by 30% (0·70 [0·63-0·78]; 1403 outcomes), and kidney failure by 34% (0·66 [0·55-0·79]; 490 outcomes). Empagliflozin slowed a chronic annual rate of eGFR decline by 64% (95% CI 59-69) and off-treatment dip-free slope—a post-hoc outcome using randomisation and off-treatment eGFR values available in a subset of 10 630 participants—by 64% (54-73). These kidney benefits were similar in subgroups divided by predicted size of acute eGFR dip, and were present irrespective of diabetes or heart failure status, level of kidney function, or albuminuria. - Interpretation - SGLT2 inhibition reduces risk of acute and chronic kidney outcomes irrespective of the size of the acute dip in eGFR. Kidney benefits are evident irrespective of diabetes status, heart failure status, primary cause of kidney disease, and markers of severity of these diseases. - Funding - None.
Online verfügbar: 11. Oktober 2025, Artikelversion: 11. November 2025
Gesehen am 15.01.2026